Deskripsi Kemampuan Komunikasi Matematika Dalam Menyelesaikan Soal Pemecahan Masalah Matematika Berdasarkan Gender - Muhammad Taqwa; Ahmad Budi Sutrisno (Jurnal Gantang, 2019)
This research is qualitative research with the aim of (1) to find out the description of mathematical communication skills of male and female students in solving mathematical problem solving questions, (2) to find out different information about mathematical communication descriptions in solving problem solving problems in terms of gender. The subjects of this study were two class VII students of SMP Negeri 2 Labakkang, namely one male and one female student who had the highest problem solving test scores. The procedure of data collection is done by observation, tests of problem solving and interviews. The research instrument was used in the form of observation sheets, tests of problem solving, interview guidelines. Data analysis techniques are carried out by testing credibility, transferbility, dependability, and conformability. The results showed that the mathematical communication skills of male gender subjects were lower than those of female gender subjects. The location of differences in mathematical communication skills between male and female gender is that the indicators write answers according to the purpose of the problem and make conclusions in writing using their own language.